Tele-ophthalmology in retinopathy of prematurity screening – A study from a referral government hospital - Bhardwaj, Prarthna V; Aradhya, Gayathri H; Reddy, Bharat; Basavaraj, A C (Indian Journal of Child Health, 2015)
Objective: The aim was to assess the role of tele-ophthalmology in retinopathy of prematurity (ROP) screening and to identify the risk factors for ROP. Design: Prospective cohort study. Setting: Level 2 neonatal intensive care unit (NICU) at a Government Hospital in Davangere, Karnataka. Subjects: 381 babies born <32 completed weeks of gestation admitted in NICU during study period. Methods: Examination of the eyes was done by a trained technician using a Ret Cam digital imaging, designed by The Karnataka Internet assisted Diagnosis of ROP, Narayana Nethralaya under the National Rural Health Mission scheme. It was later interpreted by a trained ophthalmologist using the concept of teleopthalmology. Babies were followed up and screened once weekly up to 3 months of age. Results: The overall incidence of ROP in our study was 25.2%. 3.8% of babies had Stage 1 disease, 3.8% had Stage 2, 53.8% had Stage 3, and 38.4% had Stage 4 disease. 34.2% of the babies who received oxygen therapy developed ROP. Anemia and respiratory distress syndrome have shown to significantly increase the risk of developing ROP. Two babies with ROP underwent light amplification by stimulated emission of radiation treatment and one baby underwent supplementary treatment. Conclusion: The incidence of ROP among high risk babies is significant and teleophthalmology can play a significant role in timely screening of babies in the remotest parts of the country. Oxygen therapy, anemia and respiratory distress syndrome were found to be significant independent factors predicting the development of ROP.